Bank Guarantee: Significance and Regulation Issues of the solvet et repete Principle - Nemeikšis, Giedrius (Socialiniai tyrimai, 2020)
Global economic crises, pandemic outbreaks have negative impacts not only on national economic indicators but also on the global economy, forcing businesses to suspend their activities or even close down. Therefore, upon such relations where the creditor’s confidence in the debtor has significantly decreased, the additional security of the assumed obligations becomes the factor, which enables not only the emergence of new civil legal relations but also the reduction of risk of unfulfilled agreement. For this reason, the choice of bank guarantee, as the most effective measures of the enforcement of obligations because of the solvet et repete principle become one of the most relevant issues and its demand is rising all over the world. So, this reach paper analyses three main sources of international commerce practice, which define and form the basis of bank guarantee: United Nations Convention on Independent Guarantees and Stand-by Letters of Credit, ICC Uniform Rules for Demand Guarantees and Draft Common Frame of Reference. Principles of European law. Personal security. Such tendencies of unification of bank guarantee practice in international commerce practice determine the objective necessary to analyse the compliance of the special legal regulation of bank guarantee provided in Lithuanian law with the standards set by international commerce practice, but limiting this research analysis only to the solvet et repete principle, which is specific only to bank guarantee and it is essential for the proper functioning of such a guarantee. Moreover, in order to obtain more detailed results of such analysis, the research analyses Lithuanian legal regulation practice on the issue in the context of the regulation practice of several other states with specific regulation of bank guarantee. Problematic situation: although the solvet et repete principle is a necessary basis for the proper functioning of a bank guarantee, its significance and peculiarities are emphasized in international commerce practice and legal doctrine, but Lithuanian legal doctrine does not pay any attention to this issue, considering the fact that national regulation provides separate legal provisions for a bank guarantee. The novelty of the topic: the limited research of Lithuanian legal doctrine does not analyse peculiarities of the solvet et repete principle and Lithuanian legal regulation on this question in comparison with international commerce practice and the relevant regulation practice of other countries. The legal provisions of the Civil Code of the Republic of Lithuania on bank guarantee are commented mostly in publications dedicated to the study process, that analyse in general the methods of securing obligations or international settlements, or even in the commentary of this Civil Code. However, such studies are focused only on the general introduction to peculiarities of guarantee regulation without analysing the most important principle for the proper functioning of bank guarantee. The purpose of the research is to analyse the peculiarities and regulation issues of the solvet et repete principle in international commercial practice, the legal systems of Lithuania, and other relevant countries with specific bank guarantee regulations. The objectives of the research: 1) to reveal the concept and peculiarities of the solvet et repete principle in international commercial practice; 2) to analyse the peculiarities and regulation issues of the solvet et repete principle in Lithuanian law; 3) to reveal the regulation peculiarities of the solvet et repete principle in other countries with specific bank guarantee regulations and to compare it with international standards and Lithuanian law. The research methodology: taking into account the topic, purpose and objectives of this article, the following research methods were applied: 1) the document analysis method was applied in collecting and researching data relevant to the analysis topic from international commerce practice documents and national laws; 2) the systematic analysis method was applied in the comprehensive examination of provisions of international commercial practice documents and national legal norms; 3) the comparative analysis method was applied in comparison of standards of international commerce practice with national regulations; 4) the generalization method was applied in summarizing the collected and analysed research data and formulating conclusions. Conclusions of the research: 1) the solvet et repete principle is based on the priority of the guarantor’s obligation to pay under a bank guarantee over the debtor’s ability to challenge such a payment, which is unique to the bank guarantee and essential for its proper functioning. Although this principle is individualized and analysed widely in legal doctrine, however, in analysed documents of international commerce practice this principle can be defined only by systematic analysis of separate provisions of analysed international documents. 2) A detailed analysis of the legal provisions of the Civil Code of the Republic of Lithuania on bank guarantee regulation showed that, as in case of international commerce practice, the solvet et repete principle is not expressis verbis set in legal regulation, but it can be seen from entire of relevant legal provision of this code and case law. However, the legal provision in Paragraph 5 of Article 6.92 of this Code complicates unreasonably the creditor’s ability to satisfy quickly his claim under bank guarantee, therefore its scope should be limited to the guarantor’s refusal to pay under bank guarantee only in case of a manifestly fraudulent claim. 3) The analysis of regulation peculiarities of the solvet et repete principle in other national legal systems with special bank guarantee legislation has shown that this principle is not expressis verbis set in legal regulation as in case of international commerce practice, and often the relevant national legal provisions restrict unreasonably the application of this principle, as a case of Lithuanian law, thus endangering its proper functioning. The Hungarian regulation practice is more significant than other analysed countries, because its law provides specific rules for the guarantor’s refusal to pay under bank guarantee, that strengthen significantly the solvet et repete principle, while Latvian regulation practice raises reasonable doubts regarding the proper operation of this principle, because of preventing nature of relevant legal provisions.